Occupational Health and Safety of Employees in the Czech Republic - Occupational Accident Statistics of Employees in the Czech Republic Based on Their Nationality - Josef SENČÍK; Marek NECHVÁTAL; Pavlína SEDLÁČKOVÁ; Jiří BLÁHA (Košická bezpečnostná revue, 2019)
The article deals with occupational health and safety in the Czech Republic, specifically the rate of work injury at foreigners working in the Czech Republic. Employees from selected countries were chosen for the period between 2008 and 2017. The number of accidents gained from statistical databases resulted in an analysis mapping the trends of occupational accidents in the countries of origin as well as the Czech Republic. The result points to the general conclusion that the Czech Republic has seen a decline in occupational injuries which can also be observed among most foreign employees working there. The only exception is represented by employees from Mongolia and Moldova, where occupational accident rates are on the rise. Employees from the Ukraine experienced stagnation in the chosen factors of interest.